Integrating Experience and Complexity into the Technology Acceptance Model for Health Information Systems - Muhammad Akil Hi Umar; Bangkit Sitohang (bit-Tech, 2025)
The adoption of hospital management information systems (SIMRS) has become a strategic necessity to improve service efficiency and data accuracy. Yet, user acceptance does not always align with the classical Technology Acceptance Model (TAM), especially in complex environments with diverse technological experiences. This study aims to extend TAM by introducing experience and complexity as contextual variables to assess the acceptance of the SIMRS Transmedic system at Bandung Adventist Hospital. A quantitative explanatory design was applied, and data from active SIMRS users were analyzed using Structural Equation Modeling (SEM). The findings reveal that perceived ease of use significantly influences perceived usefulness, while attitude toward use shapes behavioral intention, and both behavioral intention and perceived usefulness drive actual system use. In contrast, experience and complexity show no significant effects on perceived usefulness or ease of use. The novelty of this study lies in demonstrating that psychological factors and direct interaction with the system outweigh traditional TAM determinants in hospital settings. This challenges prevailing assumptions in prior studies that emphasize usefulness as the primary predictor of adoption. The results highlight the importance of strengthening user attitudes and experience through socialization, targeted training, and improved interface design. By providing empirical evidence on an extended TAM in healthcare, this study contributes theoretically to refining acceptance models and offers practical guidance for enhancing the effectiveness of SIMRS implementation.